Social issues of the State Border Guard Service of Ukraine personnel management - Polovnikov, V.; Половников, В.; Khalymon, S.; Халимон, С.; Komziuk, A. T.; Комзюк, А. Т.; Kopanchuk, V.; Копанчук, В.; Anatolii Komziuk (Amazonia Investiga. – 2020. – Vol. 9, Issue 29(May). – P. 395-406, 2020)
Представлено аналіз результатів опитування офіцерів Державної прикордонної служби України (ДПСУ), яке було проведено з метою вивчення сучасного стану вирішення соціально важливих для військовослужбовців ДПСУ питань, що можуть спричиняти плинність кадрів і виникнення проблемних питань у кадровому менеджменті ДПСУ. Узагальнення та інтерпретація результатів опитування дала можливість дізнатися про відношення офіцерів до служби в органах ДПСУ та оцінити стан вирішення питань соціального характеру. Зазначено, що такі обставини є одним із головних чинників того, що велика кількість військовослужбовців не бажає продовжувати контракти на проходження військової служби в ДПСУ після завершення першого контракту у молоді роки. Це має велике значення для вирішення питань кадрового забезпечення і визначення того, яким питанням слід приділити більше уваги на майбутнє, у тому числі на законодавчому рівні. Це важливо для пошуку доцільних варіантів формування змісту кадрової політики і соціально-правового забезпечення військовослужбовців ДПСУ. Наголошено, що забезпечення стабільності особового складу сприятиме підвищенню загального рівня професійної майстерності і відповідного забезпечення надійності охорони державного кордону, підвищенню ефективності протидії протиправній діяльності, управління безпекою державного кордону України у сучасних умовах.

The article presents an analysis of the results of officers’ survey of the State Border Guard Service of Ukraine (SBGSU), which was conducted to study the current state of solving socially important issues for SBGSU servicemen that may cause staff turnover and problems in SBGSU personnel management. This problem is characteristic not only to SBGSU, but also of other law enforcement agencies of Ukraine and foreign countries. To this end, the works of scientists, data statistics reports from different sources were studied, as well as the survey of 112 servicemen who are serving at the SBGSU in different positions and in different areas of professional activity was conducted.Generalization and interpreting the survey results made it possible to find out about officers’ attitudes to service at SBGSU bodies and to assess the status of social issues solving. It is concluded that such circumstances are one of the main factors that a large number of servicemen do not want to continue contracts for military service at SBGSU after the first contract closure at a young age. It has a great importance for resolving staffing issues and determining which issues should be given greater attention in future, including the legislative level. This is important for search appropriate options for the content of the personnel policy and the social and legal support of SBGSU servicemen. Stability ensuring of the personnel will help to increase the general level of professional skill and correspondingly ensure the security of the state border, increase the effectiveness of counteracting illegal activities, management of the state border security in modern conditions.

Представлен анализ результатов опроса офицеров Государственной пограничной службы Украины (ГПСУ), проведенного с целью изучения современного состояния решения социально важных для военнослужащих ГПСУ вопросов, которые могут вызывать текучесть кадров и возникновение проблемных вопросов в кадровом менеджменте ГПСУ. Обобщение и интерпретация результатов опроса позволило узнать отношение офицеров к службе в органах ГПСУ и оценить состояние решения вопросов социального характера. Отмечено, что такие обстоятельства являются одним из главных факторов того, что большое количество военнослужащих не желает продлевать контракты по прохождению военной службы в ГПСУ после завершения первого контракта в молодые годы. Это имеет большое значение для решения вопросов кадрового обеспечения и определения того, каким вопросам следует уделить больше внимания на будущее, в том числе на законодательном уровне. Это важно для поиска целесообразных вариантов формирования содержания кадровой политики и социально-правового обеспечения военнослужащих ГПСУ. Отмечено, что обеспечение стабильности личного состава будет способствовать повышению общего уровня профессионального мастерства и обеспечения надежности охраны государственной границы, повышению эффективности противодействия противоправной деятельности, управления безопасностью государственной границы Украины в современных условиях.
Соціальні питання кадрового менеджменту Державної прикордонної служби України
Keywords: Соціологія. Соціальна робота. Sociology. Social Work. Социология. Социальная работа; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Державна прикордонна служба України; State Border Service of Ukraine; Государственная пограничная служба Украины; кадрова політика; personnel policy; кадровая политика; кадровий менеджмент; personnel management; кадровый менеджмент; особовий склад; personnel; личный состав; соціальний захист; social protection; социальная защита; publikatsii u zarubizhnomu vydanni